Editorial to the Special Edition on Agriculture 4.0 of the Revista Ciência Agronômica - Dutra, Alek; Albiero, Daniel (Revista Ciência Agronômica, 2021)
EDITORIAL TO THE SPECIAL EDITION ON AGRICULTURE 4.0 OF THE REVISTA CIÊNCIA AGRONÔMICA